Arsenate and Arsenite Sorption Using Biogenic Iron Compounds: Treatment of Real Polluted Waters in Batch and Continuous Systems - Laura Castro; Lesly Antonieta Ayala; Arevik Vardanyan; Ruiyong Zhang; Jesús Ángel Muñoz (Metals, 2021)
Arsenic pollution in waters is due to natural and anthropogenic sources. Human exposure to arsenic is associated with acute health problems in areas with high concentrations of this element. Nanometric iron compounds with large specific surface areas and higher binding energy produced by some anaerobic microorganisms are thus expected to be more efficient adsorbents for the removal of harmful metals and metalloids than chemically produced iron oxides. In this study, a natural consortium from an abandoned mine site containing mainly Clostridium species was used to biosynthesize solid Fe(II) compounds, siderite (FeCO3) and iron oxides. Biogenic precipitates were used as adsorbents in contact with solutions containing arsenate and arsenite. The adsorption of As(V) fitted to the Langmuir model (qmax = 0.64 mmol/g, KL = 0.019 mmol/L) at the optimal pH value (pH 2), while the As(III) adsorption mechanism was better represented by the Freundlich model (KF = 0.476 L/g, n = 2.13) at pH 10. Water samples from the Caracarani River (Chile) with high contents of arsenic and zinc were treated with a biogenic precipitate encapsulated in alginate beads in continuous systems. The optimal operation conditions were low feed flow rate and the up-flow system, which significantly improved the contaminant uptake. This study demonstrates the feasibility of the application of biogenic iron compounds in the treatment of polluted waters.